2022
DOI: 10.1080/2162402x.2022.2127282
|View full text |Cite
|
Sign up to set email alerts
|

A novel membrane-bound interleukin-2 promotes NK-92 cell persistence and anti-tumor activity

Abstract: A major challenge in natural killer (NK) cell immunotherapy is the limited persistence of NK cells in vivo . However, the proliferation of NK cells is dependent on cytokines such as interleukin-2 (IL-2). Although IL-2 is a critical cytokine for NK cell activation and survival, IL-2 administration in adoptive NK cell therapy can induce adverse toxicities. To improve the persistence of NK cells and attenuate the systemic toxicity of IL-2, we constructed a cell-restricted artificial IL-2, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Xiong Q constructed a membrane-bound IL-2 (mbIL-2) consisting of human IL-2 and human IL-2Rα joined by a classic linker. The novel mbIL-2 improved NK-92 cell persistence and enhanced its anti-tumor activity ( 86 ). Fujii R observed that the IL-15SA/IL-15RA complex can act as an inhibitor to block the inhibitory effects of TGF-β on the NK cell activation markers CD226, NKG2D, and NKp30 in breast, lung, and prostate cancers ( 87 ).…”
Section: Regulatory Mechanisms and Research Strategies Of Nk Cells An...mentioning
confidence: 99%
“…Xiong Q constructed a membrane-bound IL-2 (mbIL-2) consisting of human IL-2 and human IL-2Rα joined by a classic linker. The novel mbIL-2 improved NK-92 cell persistence and enhanced its anti-tumor activity ( 86 ). Fujii R observed that the IL-15SA/IL-15RA complex can act as an inhibitor to block the inhibitory effects of TGF-β on the NK cell activation markers CD226, NKG2D, and NKp30 in breast, lung, and prostate cancers ( 87 ).…”
Section: Regulatory Mechanisms and Research Strategies Of Nk Cells An...mentioning
confidence: 99%